(untitled) (Al-Qamar, 2024)
The creation of Pakistan was the result of Islamic ideology. The Muslims were demanding a separate homeland where they would apply the teachings of Islam. Following Pakistan’s establishment, the principles of Islam were included in the constitution-making process in the form of an Objective Resolution. The Constitutions of 1956, 1962, and 1973 were all based solely on Islamic principles. Any laws that were considered to be anti-Islam were firmly rejected by the public at large, resulting in severe agitation. When the socialist Pakistan People’s Party tried to re-emerge in Pakistan’s political arena in 1977, Islamic ideology proved to be a binding force against PPP, prompting the formation of the Pakistan National Alliance. In 1988, the socialist PPP returned to Pakistani politics, and supporters of Islamic ideology, including the military, government, and religious political parties, formed an alliance against her, forming Islami Jamhuri Ittehad. IJI took part in elections but did not win the support of the voters. Now the question is why IJI, Pakistan’s largest religious-political alliance, was unable to defeat the PPP, a single political party. What were the reasons behind its failure? How the PPP dealt with opposition strategies in elections, including the President, Military, and IJI? What were the real causes of PPP’s success in the elections? The answers of these question are the real motive of this research.